Audit Energi Sederhana pada Pompa Distribusi Q1, Q2, dan Q3 di IPA Sunggal Perumda Tirtanadi Provinsi Sumatera Utara - Rizkia, Almira Mili; Adhi Yuniarto (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
A preliminary energy audit is a crucial step in identifying potential energy savings and improving operational efficiency in pump systems within water treatment installations. This study aims to evaluate the energy efficiency of distribution pumps Q1, Q2, and Q3 at the Sunggal Water Treatment Plant (IPA Sunggal) operated by Perumda Tirtanadi, North Sumatra Province, through a preliminary audit. The methodology includes measuring flow rate, pressure, current, voltage, and power factor to calculate hydraulic power, input power, pump efficiency, and Specific Energy Consumption (SEC). Results show that pump Q1 unit 3 and pump Q2 unit 7 have efficiencies below 60%, with SEC values indicating energy inefficiency. Improvement recommendations are provided based on efficiency criteria, ranging from impeller adjustments to complete pump replacement. This audit serves as the initial step toward a comprehensive energy audit plan to support energy efficiency and sustainability in the water distribution system.